Fostering Community-Led Waste Management Through Dynamic Governance: A Case Study of Batam City - Salsabila, Lubna; Ariany, Ria; Koeswara, Hendri (Jurnal Bina Praja, 2024)
Effective city solid waste management has become a critical issue for communities globally due to the rapid pace of urbanization and increasing environmental concerns. The convergence of economic development and environmental preservation in Batam City, Indonesia, has underscored the necessity for inventive waste management approaches. This study examines the impact of dynamic governance and community empowerment in addressing the intricate waste issue in Batam City. The research uses a qualitative approach to investigate the underlying reasons for waste management difficulties. It investigates how adaptive governance might improve stakeholder cooperation and decision-making based on facts. Effective policy implementation relies on public interaction, yet meaningful participation remains difficult. Prior research suggests that individuals are more inclined to engage in matters that directly impact them, and ambiguous implementation protocols and a lack of confidence in political establishments frequently hinder community engagement in environmental policy. The waste management techniques in Batam City are conventional and inefficient due to limited government resources, highlighting the necessity for a more comprehensive strategy. The study’s results indicate that implementing dynamic governance, which involves the flexibility to adapt and collaborate with stakeholders, can enhance waste management procedures. In addition, applying social capital theory can facilitate community empowerment, leading to a heightened sense of ownership and active engagement in waste management initiatives. Communities can enhance the effectiveness and durability of waste management systems by utilizing social networks, trust, and shared standards. This study emphasizes the significance of integrating inventive governance approaches with community-led efforts to tackle urban trash issues and advance sustainable development in Batam City.